Photothermally Activated Coacervate Model Protocells as Signal Transducers Endow Mammalian Cells with Light Sensitivity. Issue 8 (23rd June 2021) - Yao, Yu; Zhang, Yanwen; Li, Li; Huang, Yan; Yang, Xiaohai; Peng, Zhihong; Wang, Kemin; Liu, Jianbo
Abstract: The development of a novel photothermally activated coacervate model protocell is reported as a signal transducer to endow mammalian cells with light sensitivity. In this system, near‐infrared light irradiation triggers H2 S release in coacervate model protocells, leading to modulation of the behavior of living cells. The functional coacervate model protocells are prepared by loading metal‐alloyed plasmonic nanoparticles and an H2 S donor into the liquid coacervate microdroplets. Upon light irradiation, the H2 S signal messenger is released through the photothermal effect of plasmonic nanoparticles and photothermal mediated pyrolysis of the H2 S donor. The H2 S signal is delivered to the mammalian cell community to trigger depletion of reactive oxygen species, reduce the activity of lactate dehydrogenase and improve cell viability. This study provides a new approach to the implementation of chemical signaling in artificial cell colonies and protocell/living cell consortia. The photothermal protocell system offers a powerful platform for light modulation of the behavior of mammalian cells and shows great promise for biomedical applications. Abstract : An engineered ecosystem in which light‐responsive artificial cells produce signals to which mammalian cells respond. This system is implemented without the need for genetic manipulation, offering an easy and practical method for remote control of cellular behavior.